The persistence of microvascular dysfunction is associated with a worse outcome in patients with severe sepsis (2010)
The persistence of microvascular dysfunction is associated with a worse outcome in patients with severe sepsis. Elaborado por Gustavo Adolfo Ospina,Jacques Creteur, Ana P. Neves, Daniel De Backer, Jean Luis Vincent, publicado por Sppringer